Analisis Kepastian Hukum Terhadap Korban Penipuan Doni Salmanan Ditinjau Dari Putusan Pengadilan Negeri Bale Bandung Nomor 576/Pid.Sus/2022/PN Blb - Adilah Rahman; Adisty Maharani; Anzira Sania Desivha; Reza Dio Wijatmika; Herli Antoni (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This research examines more deeply the analysis of legal certainty for victims of Doni Salmanan's fraud in trading through an application called QUOTEX. In relation to the decision of the Bale Bandung District Court number 576/Pid.Sus/2022/PN BlB, in which the Panel of Judges gave a verdict of imprisonment and confiscation of assets owned by the defendant generated through trading by utilizing his victims for profit and the assets were confiscated by the state. However, in the verdict there was no decision at all to provide compensation to the victim of Doni Salmanan's fraud, in this case the element of legal justice for the victim was not fulfilled by this decision. However, the aspect of legal certainty for the victim is very strong so that the defendant gets a death sentence and a fine for his actions. The legal certainty in question is a guarantee that the law is carried out properly in processing the rights and obligations of the defendant for his crime. Material law as an element of legal certainty has been carried out and linked to various laws and regulations relating to the case. Law No. 8/1999 on Consumer Protection for the losses suffered by the victim as a consumer, Law No. 19/2016 on the Amendment to Law No. 11/2008 on Electronic Information and Transactions because the case involved electronic networking devices, and Law No. 8/2010 on the Prevention and Eradication of the Crime of Money Laundering because in the prosecution the defendant was deemed to have disguised his wealth generated through criminal acts.